Continuous flow reactor based with an immobilized biocatalyst for the continuous enzymatic transesterification of crude coconut oil. (30th January 2020) - Santana, Juliana L.; Oliveira, Juliana M.; Nascimento, Jamily S.; Mattedi, Silvana; Krause, Laiza C.; Freitas, Lisiane S.; Cavalcanti, Eliane B.; Pereira, Matheus M.; Lima, Álvaro S.; Soares, Cleide M. F.
Abstract: Here, we have assessed the use of one packed bed or two packed bed reactors in series in which Burkholderia cepacia lipase (BCL) was immobilized on protic ionic liquid (PIL)‐modified silica and used as a biocatalyst for the transesterification of crude coconut oil. Reaction parameters including volumetric flow, temperature, and molar ratio were evaluated. The conversion of transesterification reaction products (ethyl esters) was determined using gas chromatography and the quantities of intermediate products (diglyceride and monoglyceride [MG]) were assessed using high‐performance liquid chromatography. Packed bed reactors in series produced ethyl esters with the greatest efficiency, achieving 65.27% conversion after 96 H at a volumetric flow rate of 0.50 mL Min −1 at 40 °C and a 1:9 molar ratio of oil to ethanol. Further, within the first 24 H of the reaction, increased MG (54.5%) production was observed. Molecular docking analyses were performed to evaluate the catalytic step of coconut oil transesterification in the presence of BCL. Molecular docking analysis showed that triglycerides have a higher affinity energy (−5.7 kcal mol −1 ) than the smallest MG (−6.0 kcal mol −1 ), therefore, BCL catalyzes the conversion of triglycerides rather than MG, which is consistent with experimental results. Abstract : The continuous single and series packed bed reactor were used in the enzymatic transesterification reaction of crude coconut oil and ethanol for the production of ethyl esters and monoglycerides. Molecular docking was used to analyze the catalytic steps of the transesterification reaction.